Catalytic enantioselective intramolecular Tishchenko reaction of meso-dialdehyde: synthesis of (S)-cedarmycins. Issue 19 (22nd March 2021) - Ismiyarto; Kishi, Nobuki; Adachi, Yuki; Jiang, Rui; Doi, Takahiro; Zhou, Da-Yang; Asano, Kaori; Obora, Yasushi; Suzuki, Takayoshi; Sasai, Hiroaki; Suzuki, Takeyuki
Abstract : The first successful example of a catalytic enantioselective intramolecular Tishchenko reaction of a meso -dialdehyde in the presence of a chiral iridium complex is described. Abstract : The first successful example of a catalytic enantioselective intramolecular Tishchenko reaction of a meso -dialdehyde in the presence of a chiral iridium complex is described. Chiral lactones were obtained in good yields with up to 91% ee. The obtained enantioenriched lactones were utilized for the first synthesis of ( S )-cedarmycins A and B.